Penerapan Informasi Akuntansi Manajemen Dalam Proses Pengambilan Keputusan Menghentikan Atau Meneruskan Produk Pada Depot Muhajirin - Nur Amilia Khasanah (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
ABSTRACTManagement accounting is an accounting system that deals with the provision and use of accounting information to present the form of a business unit report for internal purposes, namely managers or management in an organization and provides the basis for management to make business decisions. Management accounting has the main function of assisting in making decisions regarding the use of funds for organizational purposes. This is because management accounting provides an analysis of the profits and losses experienced by the organization and the factors that support it. This study aims to determine management accounting information in the decision-making process to stop or continue the product at Depon Muhajirin by using an alternative calculation of unavoidable fixed costs and unavoidable fixed costs. The type of research used is descriptive qualitative research. The results of this study indicate that the results of the analysis of unavoidable fixed costs and unavoidable fixed costs of decision making to stop or continue brown bread products, choose the alternative to continue brown bread production because the decision to discontinue chocolate bread products will actually cause a decrease in profit by the contribution margin of brown bread. amounting to Rp.2,720,000, so that the decision for chocolate bread products is to continue production.Keywords : Management Accounting Information, Decision Making to Continue or Discontinue Products. Avoidable Fixed Costs and Inevitable Fixed Costs